Seasonal communication about dengue fever in educational groups in primary healthcare - Silva, Líliam Barbosa; Soares, Sônia Maria; Fernandes, Maria Teresinha de Oliveira; Aquino, Ana Luiza de (Revista de Saúde Pública, 2011)
OBJECTIVE: To analyze how seasonal communication for dengue control and prevention is conveyed in educational peer groups of Family Health teams. METHODOLOGICAL PROCEDURES: An exploratory and descriptive qualitative study was performed with 25 coordinators of peer education groups, distributed among eight basic health units of Belo Horizonte, Southeastern Brazil. Data collection occurred from March to June 2009, by non-participant observation and semi-structured interviews with coordinators. Content analysis and the principal theories in health communication were utilized in data interpretation. ANALYSIS OF RESULTS: Three thematic units were identified: seasonal communication; subjects discussed and information sources about dengue; and information versus communication for action. Dengue prevention and control actions were principally discussed in groups during outbreaks, based on actions previously programmed by the Ministry of Health. The topics addressed focused on epidemiology, life cycle, modes of transmission, symptoms, prevention, domiciliary visits by zoonosis control units and vaccination for dengue. CONCLUSIONS: The predominant communication action is information conveyance by the coordinator, centered on a behavioralist and prescriptive discourse. Communication practices focused on dialogue is recommended, allowing the coordinator and group members freedom in regards to emergent issues in the group, so they learn to recognize and reflexively discuss them in context.